SYSTEM GEOBRANDING IN THE DEVELOPMENT OF INNOVATIVE ECONOMY OF THE REGION - Arpentieva, M.R. (Perm Federal Research Centre Journal, 2016)
The article describes the main aspects and the role of geobranding in the economic development of the region. The main approaches to the study and practical implementation of geobranding are analyzed, the most distinguished, in the author’s view, aspects of productivity and efficiency of geobranding, as a component of regional economic development, are presented. The importance of the development of geobranding and implementation of rebranding of territories is emphasized, the leading principles and aspects of branding are highlighted. Systemic methodology of geobranding take into account the needs of all interested groups (stakeholders).